Problems among childrens with impaired hearing. The impact of noise on the work of teachers - Kucharska, Ewelina Karolina (Journal of Education, Health and Sport, 2017)
Introduction and Aim In the life of every human senses, including the sense of hearing, they play an important role in the harmonious development. Each hearing loss in childhood influences, depending on the depth, nature and time of its inception, in a negative way on the development of many mental activities, intellectual, behavior, cognitive, causing significant impairment in the child’s position the hearing impaired, deaf and especially in the world of the hearing. The aim of this study is to assess the parents’ awareness of hearing loss in children with hearing loss as a result of a survey of parents of children from the first classes of primary schools in the Lublin province. Material and Methods Analysis was performed on 31 results of parents of children with hearing impairment made in children aged 6 and 7 years, pupils and primary schools in the Lublin province. Parents were asked the question: ’Do you think your child has hearing problems?’ The analysis indicated the assessment of awareness of parents of children with hearing disorders. Results In the study group, as many as 77% of parents stated that the child does not have problems with hearing, only 3% of parents noted the problem, while 20% of parents did not answer the question. Conclusions Based on the research it can be stated with a high percentage of parents still do not notice hearing loss in their children. Early notice of the problem, the correct procedure and the cooperation with the parent group of specialists are often the way to success. It is crucial to support the child in difficult situations, which often is exposed to contact with all sorts of obstacles. An important issue is the numerous health programs, shaping the attitude of parents and society as a whole.